2023
DOI: 10.3390/ijms241914471
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Fullerene Potentially Inhibits SARS-CoV-2 Infection by Modulating Spike Protein Conformational Changes

Kaifeng Liu,
Fangfang Guo,
Yingying Ma
et al.

Abstract: The disease of SARS-CoV-2 has caused considerable morbidity and mortality globally. Spike proteins on the surface of SARS-CoV-2 allow it to bind with human cells, leading to infection. Fullerenes and their derivatives are promising SARS-CoV-2 inhibitors and drug-delivery vehicles. In this study, Gaussian accelerated molecular dynamics simulations and the Markov state model were employed to delve into the inhibitory mechanism of Fullerene–linear-polyglycerol-b-amine sulfate (F–LGPS) on spike proteins. During th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…For trajectory examination, we conducted K-means clustering, utilizing the Cpptraj module within Amber16 [ 61 ]. The MM-PBSA method facilitated the computation of binding free energies, a crucial determinant in the evaluation of protein–protein affinities [ 62 , 63 , 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…For trajectory examination, we conducted K-means clustering, utilizing the Cpptraj module within Amber16 [ 61 ]. The MM-PBSA method facilitated the computation of binding free energies, a crucial determinant in the evaluation of protein–protein affinities [ 62 , 63 , 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similar to our previous work [72], we employed the molecular mechanics/Poisson-Boltzmann surface area (MM/PBSA) method to investigate the binding affinity between kaempferol and PTP1B. The binding free energy (∆G bind ) is represented by the following formula:…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Changes in Rg and conformation post-binding altered the binding poses. The Solvent Accessible Surface Area (SASA) indicated that T1R2 combined with IGR and T1R3 with GGR had lower SASA, potentially indicating a tighter binding [26,27].…”
Section: Peptides Screening Based On Structurementioning
confidence: 99%
“…Changes in Rg and conformation postbinding altered the binding poses. The Solvent Accessible Surface Area (SASA) indicated that T1R2 combined with IGR and T1R3 with GGR had lower SASA, potentially indicating a tighter binding [26,27]. The MM-PBSA method provided a more accurate prediction of binding energy, as it is based on multiple structure calculations, accounting for dynamic changes during binding.…”
Section: Peptides Screening Based On Structurementioning
confidence: 99%